"China loves Italy": transnational co-productions between China and Italy behind the mask of market†. Issue 1 (2nd January 2017) - Fu, Yongchun; Indelicato, Maria Elena
ABSTRACT: Since the term "transnational cinema" first appeared in 1997, most studies have focused on films epitomizing the logic of either profit maximization or ethnic affinity to explain phenomena such as the mainstreaming of Kung Fu movies. Yet, these two logics do not account for the entirety of the transnational projects that have been produced to date, hence the call for more studies on "trans-border patterns" that operate beyond both of them (Berry 2010, 123). In this article, we take up this call and approach the co-productions between China and Italy as exhibiting a "trans-border pattern" which satisfies interests beyond both the market and ethnic affinity. We trace the history of such a "pattern" back to the arrival of the Italian pioneer of Chinese cinema, Amerigo Lauro, in Shanghai in the early 1900s. We contextualize the productions of Michelangelo Antonioni's Chung Kuo/China (1973), Giuliano Montaldo's Marco Polo (1982) and Bernardo Bertolucci's The Last Emperor (1987) to provide exemplary cases of a non-market oriented affinity between two culturally distinct nations: China and Italy. We conclude by suggesting that China has pursued transnational co-productions with European countries such as Italy to exercise a more productive control than censorship over the ways China is to be represented internationally.